Negative pole piece and preparation method thereof

By using the dual-layer active material structure of alloy A and hard carbon supported by carbon material in the negative electrode sheet of lithium-ion battery, the problem of being unable to achieve high energy density and high rate performance at the same time in the prior art is solved, and the battery is realized. The effect of taking into account both fast charging capability and energy density.

CN119480909APending Publication Date: 2025-02-18ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411576946.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The negative electrode sheets of existing lithium-ion batteries cannot achieve high energy density and high rate performance at the same time, resulting in insufficient battery fast charging capability and energy density.

Method used

The two-layer active material structure consisting of alloy A and hard carbon supported by carbon material. The precursor E of alloy A includes Si, Ge, Sn, Fe, Cu, P and other elements and carbon-containing substance B are calcined. The porosity of carbon is 30% to 50%, and nitrogen or phosphorus elements are doped in hard carbon to improve the conductivity and the first effect of lithium-ion batteries.

Benefits of technology

Through synergistic effects, high energy density and high rate performance are achieved, and the cycle life of lithium-ion batteries and the rate performance of fast charging and discharge are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005122019380000141
    Figure BDA0005122019380000141
  • Figure BDA0005122019380000151
    Figure BDA0005122019380000151
  • Figure BDA0005122019380000161
    Figure BDA0005122019380000161
Patent Text Reader

Abstract

The invention provides a negative pole piece and a preparation method thereof, the negative pole piece comprises a current collector, a first active material layer and a second active material layer, the current collector is coated with the first active material layer and the second active material layer in sequence, and the gram volume of the first active material layer is larger than that of the second active material layer. The expansion rate of the first active material layer is greater than that of the second active material layer; the first active material layer comprises an alloy A supported by a carbon material; the second active material layer includes hard carbon. According to the negative pole piece, the alloy A supported by the carbon material combined by different alloys is prepared, so that the alloy A supported by the carbon material has different expansion coefficients and gram volumes, and the larger the gram volume is, the larger the energy density is; by preparing the N-doped and P-doped hard carbon, the conductivity of the material and the first effect of the lithium ion battery can be greatly improved, electron and lithium ion transport channels in the hard carbon are increased, the capacity of the material is effectively improved, and the performance of the battery adopting the negative pole piece is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium-ion batteries, and in particular relates to a negative electrode plate and a preparation method thereof. Background Art

[0002] Nowadays, lithium-ion batteries have become energy storage devices for mainstream electronic products. While people are raising their requirements for the energy density of lithium-ion batteries, their requirements for fast charging capabilities, that is, rate performance, are also becoming higher and higher. Energy density refers to the amount of electrical energy that can be stored per unit volume or mass of a battery. Rate performance refers to the reversible specific capacity retention rate when charging and discharging at a 1C rate current relative to a 0.1C rate current. For lithium-ion batteries, the energy density and rate of lithium-ion batteries are two diametrically opposed directions. Generally, the greater the energy density of a battery, the lower its rate performance, and it is impossible to achieve a balance between fast charging capabilities and energy density.

[0003] Chinese patent CN 117652038 A discloses an electrode assembly, a secondary battery, a battery module, a battery pack and an electrical device, wherein the electrode assembly includes a negative electrode plate, wherein the negative electrode plate includes a negative electrode collector and a first negative electrode film layer and a second negative electrode film layer arranged on at least one surface of the negative electrode collector, the first negative electrode film layer is located between the negative electrode collector and the second negative electrode film layer and includes a first negative electrode active material, the first negative electrode active material includes graphite, the second negative electrode film layer includes a second negative electrode active material, the second negative electrode active material includes hard carbon, in this prior art, but the combination of graphite and hard carbon cannot achieve high energy density and high rate performance at the same time through a synergistic effect. Summary of the invention

[0004] The purpose of the present invention is to provide a negative electrode plate to address the deficiencies of the prior art, wherein the negative electrode plate can achieve high energy density and high rate performance simultaneously through a synergistic effect.

[0005] In order to achieve the above-mentioned object, the present invention adopts a negative electrode plate, the negative electrode plate comprises a current collector, a first active material layer and a second active material layer are sequentially coated on the current collector, the first active material layer is located between the current collector and the second active material layer, the gram capacity of the first active material layer is greater than the gram capacity of the second active material layer, and the expansion rate of the first active material layer is greater than the expansion rate of the second active material layer; the first active material layer comprises an alloy A supported by a carbon material; the second active material layer comprises hard carbon; the alloy A comprises Si x M y, wherein x:y is 0.05mol~0.2mol:0.05mol~1.4mol, wherein M includes three or more elements selected from vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, arsenic, aluminum, phosphorus, boron, ruthenium, rhodium, palladium, silver, cadmium, indium, tin, antimony, rhenium, osmium, iridium, platinum and gold, and M includes at least one element selected from vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, aluminum, ruthenium, rhodium, palladium, silver, cadmium, indium, tin, antimony, rhenium, osmium, iridium, platinum and gold.

[0006] It should be noted that the alloy A refers to a solid solution alloy composed of four or more elements, with the content ratio of the constituent elements being an equiatomic ratio or a non-equiatomic ratio, and the phase structure being a single-phase, two-phase or multi-phase. As long as the carbon material meets the condition that it can support alloy A, it falls within the protection scope of the present invention.

[0007] Furthermore, the carbon material-supported alloy A is formed by calcining the precursor E of the alloy A and a carbon-containing substance B, wherein the carbon-containing substance B includes one or more of MOFs, carbon black, sodium lignin sulfonate, sodium alginate, sodium polyacrylate, alkali lignin, sodium citrate, sodium polystyrene sulfonate and sodium acrylate, and the metal elements in the MOFs are composed of one or more of vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, aluminum, ruthenium, rhodium, palladium, silver, cadmium, indium, tin, antimony, rhenium, osmium, iridium, platinum and gold.

[0008] Furthermore, the mass ratio of the precursor E of the alloy A to the carbon-containing substance B is 7:1 to 1:1.

[0009] Furthermore, the mass ratio of the precursor E of the alloy A to the carbon-containing substance B is 7:1, 7:2, 6:1, 5:1, 4:1, 7:2, 3:1, 2:1, 7:4 or 1:1, etc.

[0010] Furthermore, the porosity of the hard carbon is 30% to 50%, and / or,

[0011] The hard carbon contains nitrogen and / or phosphorus, the mass percentage of nitrogen doping is 1.5% to 2.7%, and the mass percentage of phosphorus doping is 1.0% to 2.0%.

[0012] Furthermore, in the hard carbon, the nitrogen source is a nitrogen-containing compound or multiple nitrogen-containing compounds composed of one or several elements among C, O and H and N element, and the phosphorus source is a phosphorus-containing compound or multiple phosphorus-containing compounds composed of one or several elements among C, O and H and P element, and the multiple types are two to five types. The use of the above-mentioned nitrogen source and / or phosphorus source can avoid the introduction of impurity elements, and those skilled in the art can select from the above-mentioned compounds according to actual needs.

[0013] It should be noted that doping the hard carbon with nitrogen and / or phosphorus can improve the electrical conductivity of the material and the initial efficiency of the lithium-ion battery, increase the electron and lithium ion transport channels in the hard carbon, and effectively improve the capacity of the material, thereby greatly improving the performance of the battery using the negative electrode plate.

[0014] Furthermore, the first active material layer and the second active material layer both include a dispersant and a binder, the mass fraction ratio of the alloy A supported by the carbon material: the dispersant: the binder is 95% to 98%: 1.0% to 3.5%: 1.0% to 1.5%, and the mass fraction ratio of the hard carbon: the dispersant: the binder is 95% to 98%: 1.0% to 3.5%: 1.0% to 1.5%. Specifically, the dispersant is carboxymethyl cellulose, and the binder is styrene-butadiene rubber.

[0015] Furthermore, the mass fraction ratio of alloy A supported by the carbon material: dispersant: binder is 96%:2.5%:1.5%, and the mass fraction ratio of hard carbon: dispersant: binder is 96%:2.5%:1.5%.

[0016] Furthermore, the surface density of the first active material layer is greater than the surface density of the second active material layer, the compaction density of the first active material layer is greater than the compaction density of the second active material layer, and the current collector includes copper foil or aluminum foil.

[0017] It should be noted that the compaction density of the second active material layer of the negative electrode plate is lower than that of the first active material layer, which results in that during the reaction, the energy density of the first active material layer is greater than the energy density of the second active material layer, and the rate performance of the second active material layer is greater than the rate performance of the first active material layer. Therefore, the negative electrode plate has an overall rate performance improved due to the high rate performance of the second active material layer, and has an overall energy density improved due to the high energy density of the first active material layer.

[0018] Furthermore, the surface density of the first active material layer is 0.050 g / 1540.25 mm 2 ~0.070g / 1540.25mm 2 , compacted density is 1.40g / cm 3 ~1.90g / cm 3 , and / or,

[0019] The surface density of the second active material layer is 0.044 g / 1540.25 mm 2 ~0.054g / 1540.25mm 2 , compacted density is 1.20g / cm 3 ~1.80g / cm3 ,

[0020] Furthermore, the surface density of the first active material layer is 0.060 g / 1540.25 mm 2 , compacted density is 1.70g / cm 3 The surface density of the second active material layer is 0.054 g / 1540.25 mm 2 , compacted density is 1.60g / cm 3 .

[0021] A method for preparing the negative electrode sheet in any of the above schemes, comprising the steps of:

[0022] Prepare the carbon material-supported alloy A; use the carbon material-supported alloy A to prepare a first slurry; use hard carbon to prepare a second slurry; uniformly apply the first slurry on the upper and lower surfaces of the current collector by extrusion coating to prepare the first active material layer, and uniformly apply the second slurry on the outer surface of the first active material layer by extrusion coating to prepare the second active material layer, thereby preparing the negative electrode sheet.

[0023] Furthermore, the carbon material-supported alloy A is prepared by the following steps:

[0024] In step S1, a silicon element and a metal salt C are subjected to ball milling reaction to generate a precursor E, which is then impregnated with the carbon-containing substance B, freeze-dried, crushed, and then calcined. The metal salt C includes three or more elements selected from vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, arsenic, aluminum, phosphorus, boron, ruthenium, rhodium, palladium, silver, cadmium, indium, tin, antimony, rhenium, osmium, iridium, platinum, and gold;

[0025] Or in step S1, silicon element, metal salt C and non-metallic pure substance D are subjected to ball milling reaction to generate precursor E, which is then impregnated with the carbon-containing substance B, freeze-dried, crushed and calcined. The metal salt C and non-metallic pure substance D include three or more elements of vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, arsenic, aluminum, phosphorus, boron, ruthenium, rhodium, palladium, silver, cadmium, indium, tin, antimony, rhenium, osmium, iridium, platinum and gold, and the metal salt C must include one element of vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, aluminum, ruthenium, rhodium, palladium, silver, cadmium, indium, tin, antimony, rhenium, osmium, iridium, platinum and gold.

[0026] Furthermore, the hard carbon is prepared by the following method:

[0027] The biomass raw material is first crushed into small particles, washed and dried to obtain a precursor I, and then a nitrogen-containing compound and / or a phosphorus-containing compound is added to the precursor I, carbonized for t1 time under a protective atmosphere and a temperature T, and then heated in a tubular furnace and ball-milled for t2 time at a rotation speed m, and then the product is passed through a 325-mesh sieve.

[0028] Furthermore, the biomass raw material includes one of bagasse, rice husk, coconut shell, bamboo, nut shell, cotton, cherry wood, and cucumber vine; the particle size of the small particles is 2 to 10 mm, the drying temperature is 100° C. to 120° C., and the drying time is 36 h to 48 h; the nitrogen-containing compound includes urea, and the phosphorus-containing compound includes phosphoric acid; T is 1000° C. to 1200° C., t1 is 3 h to 5 h, and the heating rate in the tube furnace is 5° C. min -1 ~8℃·min -1 , nitrogen flow rate is 150mL·min -1 ~180mL·min -1 , m is 270r·min -1 ~300r·min -1 , t2 is 8h~12h.

[0029] Furthermore, in step S1, the metal salt C includes sulfate, nitrate or chloride.

[0030] Furthermore, in step S1, the carbon-containing substance B includes one or more of MOFs, carbon black, sodium lignin sulfonate, sodium alginate, sodium polyacrylate, alkali lignin, sodium citrate, sodium polystyrene sulfonate and sodium acrylate, and the metal elements in the MOFs are composed of one or more of vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, aluminum, ruthenium, rhodium, palladium, silver, cadmium, indium, tin, antimony, rhenium, osmium, iridium, platinum and gold.

[0031] It should be noted that the above-mentioned carbon-containing substances B can be selected in any type and any proportion within the protection scope of the present invention, and within the protection scope of the technical scheme of the present invention, the mass ratio of one or several selected carbon-containing substances B to the precursor E of the alloy A can realize the technical scheme of the present invention, because the above-mentioned carbon-containing substances B can form the carbon material supporting the alloy A in the independent claim of the present invention.

[0032] Furthermore, in step S1, the ball milling time of the precursor E of the alloy A is 8 h to 20 h, and the ball milling speed is 300 rpm / min to 500 rpm / min.

[0033] Furthermore, in step S2, during impregnation, the mass ratio of the precursor E of the alloy A to the carbon-containing substance B is 7:1 to 1:1, the impregnation time is 5 h to 10 h, and the calcination step comprises: pyrolysis in a tubular furnace at 700° C. to 900° C. under a protective atmosphere while maintaining the protective atmosphere flowing, and the heating rate is 5° C. min -1 ~10℃·min -1 The stay time is 2h to 4h.

[0034] Furthermore, the mass ratio of the precursor E of the alloy A to the carbon-containing substance B is 7:4.

[0035] Furthermore, the protective atmosphere is an argon atmosphere, a helium atmosphere or a nitrogen atmosphere, and the flow rate of the protective atmosphere adopts the flow rate in the prior art. Those skilled in the art can select the flow rate in the prior art according to actual needs to achieve the purpose of deoxygenation.

[0036] Furthermore, the preparation method also includes

[0037] Prepare the first slurry: mix and stir the dispersant and the alloy A supported by the carbon material evenly, wherein the dispersant used here is carboxymethyl cellulose, and finally add a binder, wherein the binder used here is styrene-butadiene rubber, and stir to obtain the first slurry; the mass fraction ratio of the alloy A supported by the carbon material: carboxymethyl cellulose: styrene-butadiene rubber is 95% to 98%: 1.0% to 3.5%: 1.0% to 1.5%; and / or,

[0038] Prepare the second slurry: mix the carboxymethyl cellulose and the hard carbon and stir them evenly, finally add styrene-butadiene rubber and stir to obtain the second slurry, wherein the mass fraction ratio of the hard carbon: carboxymethyl cellulose: styrene-butadiene rubber is 95% to 98%: 1.0% to 3.5%: 1.0% to 1.5%.

[0039] It should be noted that the preparation method of the negative electrode plate proposed in the present invention uses the alloy supported by the carbon material as the bottom layer of the double-layer coating, which can provide a higher energy density. At the same time, using hard carbon as the top layer can improve the conductivity of the material. If the hard carbon is further doped with N and P, it will have a greater impact on the fast charging performance of the material and can improve the fast charging performance of the material. The preparation method designs slurries with different conductive properties in the slurry mixing stage. The process is simple and easy to mass-produce on a large scale. The bottom and upper layers of the double-layer coating process are also designed in proportion, for example, 1:1. The double-layer coating is simple to control, and the surface density calculation and control are simple.

[0040] Beneficial Effects

[0041] Compared with the prior art, the present invention has at least the following beneficial effects:

[0042] 1. A negative electrode plate proposed in the present invention is prepared by preparing an alloy A supported by a carbon material composed of different alloy combinations, so that the alloy A supported by the carbon material has different expansion coefficients and gram capacities. The larger the gram capacity, the greater the energy density. The components of the alloy are closely connected and coordinated in stages, multiple levels and multiple platforms, thereby avoiding the concentrated volume explosion of a single component. The conductivity of the negative electrode material is improved by using hard carbon as the top layer.

[0043] 2. The negative electrode plate proposed in the present invention is a silicon-based negative electrode material. Compared with commercial graphite negative electrodes (372mAh / g), alloy materials represented by silicon-based (4200mAh / g) have become candidates for the next generation of negative electrode materials due to their larger discharge capacity and higher lithium storage activity. However, alloy materials represented by silicon-based (4200mAh / g) will still experience huge stress strain and volume expansion during the charging and discharging process, with a volume expansion coefficient of up to 400%, causing the active material to suffer serious crystal structure damage, particle morphology collapse, and electrode powdering and shedding, ultimately leading to rapid attenuation of the battery's cycle life and rapid charge and discharge rate performance. When used as a lithium battery negative electrode, low-expansion, high-capacity alloy A exhibits a larger discharge capacity (>1500mAh / g), a lower voltage platform (0-0.5V) and a higher first coulombic efficiency (ICE>85%). DETAILED DESCRIPTION

[0044] The present invention will be described in further detail below in conjunction with specific implementation modes, but the implementation modes of the present invention are not limited thereto.

[0045] Example 1

[0046] Preparation of low-expansion and high-capacity precursor E: Si and CuCl2·2H2O, Ge, SnCl4·5H2O, FeCl3·6H2O, and P were mixed by a typical high-energy mechanical ball milling method. The raw materials were continuously ball milled for 15 h at a speed of 400 rpm / min to synthesize Ge-Sn-Si-Fe-Cu-P precursor E with a molar ratio of 0.2:0.1:0.05:0.05:0.05:1.

[0047] Synthesis of carbon material supported alloy A: The above-mentioned precursor E and carbon black were impregnated at a mass ratio of 7:4 for 10 hours. Then, the product was completely freeze-dried to obtain powder F, which was properly crushed with a mortar and pestle, and then pyrolyzed in a tube furnace at 900°C in an argon environment, and high-purity argon was kept flowing during the pyrolysis process. The heating rate and the maximum temperature were 10°C / min and 900°C, respectively, and the residence time was 2 hours, and the carbon material supported alloy A was obtained.

[0048] Preparation of hard carbon with high porosity: First, the coconut shell was crushed into particles of 2 to 10 mm, washed with deionized water three times, and then dried in a vacuum oven at 120°C for 36 hours. 200 g of hard carbon precursor was obtained. In addition, 10 g of urea and 10 g of phosphoric acid were used as nitrogen and phosphorus sources to introduce N (nitrogen) and P (phosphorus) heteroatoms into the hard carbon matrix to change its structure. The mass percentage of N doping was 2.1% and the mass percentage of P doping was 1.4%. Then, it was carbonized at 1000°C for 5 hours in a nitrogen atmosphere, and the heating rate in a tubular furnace was 5°C min -1 , nitrogen flow rate is 150mL·min -1. Finally, at 270 r / min -1 The carbonized particles were ball milled at a rotation speed of 12 h, and then the product was passed through a 325-mesh sieve, and the porosity of the hard carbon was controlled at 40%.

[0049] Preparation of the first slurry: The components and proportions of the first slurry are 96wt% of alloy A supported by carbon material, 2.5wt% of carboxymethyl cellulose and 1.5wt% of styrene-butadiene rubber. The carboxymethyl cellulose and the alloy A supported by carbon material are mixed and stirred evenly, and finally styrene-butadiene rubber is added and stirred to obtain the first slurry.

[0050] Preparation of the second slurry: The components and proportions of the second slurry are 96wt% of high-porosity hard carbon, 2.5wt% of carboxymethyl cellulose and 1.5wt% of styrene-butadiene rubber. The carboxymethyl cellulose and high-porosity hard carbon are mixed and stirred evenly, and finally styrene-butadiene rubber is added and stirred to obtain the second slurry.

[0051] Double-layer coating: A 6 μm thick copper foil was used as the current collector. The first slurry was uniformly coated on the upper and lower surfaces of the current collector by extrusion coating. The surface density of the first active material layer prepared was 0.060 g / 1540.25 mm 2 , compacted density is 1.80g / cm 3 The obtained second slurry is uniformly coated on the outer surface of the first active material layer by extrusion coating, and the surface density of the prepared second active material layer is 0.054g / 1540.25mm 2 , compacted density is 1.70g / cm 3 The coating thickness ratio can be calculated based on the surface density and compaction: single-sided thickness (excluding copper foil) = CW*1000 / (compacted density*1540.25).

[0052] The lithium battery of this embodiment uses the lithium battery negative electrode sheet prepared in this embodiment, and also includes a positive electrode sheet, a separator, an electrolyte, and a shell structure, and the cycle performance at room temperature is tested.

[0053] Example 2

[0054] The preparation method is consistent with that of Example 1, except that in the second step of Example 2, the carbon material-supported alloy A is synthesized, and the mass ratio of precursor E to carbon-containing material is 1:1.

[0055] Example 3

[0056] The preparation method is consistent with that of Example 1, except that in the second step of Example 3, the carbon material-supported alloy A is synthesized, and the mass ratio of precursor E to carbon-containing material is 7:1.

[0057] Example 4

[0058] The preparation method is consistent with that of Example 1, except that in Example 4, the amount of phosphoric acid added is 14.3 g, and the amount of P doped is 2.0%

[0059] Example 5

[0060] The preparation method is consistent with that of Example 1, except that in Example 5, the amount of phosphoric acid added is 7.1 g, and the amount of P doped is 1.0%.

[0061] Example 6

[0062] The preparation method is consistent with that of Example 1, except that in Example 6, the amount of urea added is 12.9 g and the amount of N doping is 2.7%.

[0063] Example 7

[0064] The preparation method is consistent with that of Example 1, except that in Example 7, the amount of urea added is 7.1 g, and the doping amount of N is 1.5%.

[0065] Example 8

[0066] The preparation method is consistent with that in Example 1, except that in Example 8, the molar ratio of various materials is changed in the step of synthesizing precursor E, and a Ge-Sn-Si-Fe-Cu-P precursor E with a molar ratio of 0.03:0.01:0.05:0.11:0.01:0.05 is synthesized.

[0067] Example 9

[0068] The preparation method is consistent with that in Example 1, except that in Example 9, various materials and their molar ratios are changed in the step of synthesizing precursor E, and Si, Mn(NO3)2, P and B are mixed by ball milling. The raw materials are continuously ball milled for 8 hours at a rotation speed of 300 rpm / min to synthesize Mn-Si-BP precursor E with a molar ratio of 0.2:0.1:0.1:0.1.

[0069] Example 10

[0070] The preparation method is consistent with that in Example 1, except that in Example 10, various materials and their molar ratios are changed in the step of synthesizing precursor E, and Si, P, VSO4·7H2O, Cr2(SO4)3, Fe2(SO4)3, CuSO4, ZnSO4, Ga2(SO4)3, Ge(SO4)2 and Al2(SO4)3 are mixed by ball milling. The raw materials are continuously ball milled for 20 hours at a speed of 500 rpm to synthesize V-Cr-Fe-Cu-Si-Zn-Ga-Ge-Al-P with a molar ratio of 0.01:0.02:0.02:0.02:0.02:0.02:0.02:0.02:0.12.

[0071] Embodiment 11

[0072] The preparation method is consistent with that in Example 1, except that in Example 11, various materials and their molar ratios are changed in the step of synthesizing precursor E, and Si, P, RuCl3·3H2O, PdCl2, AgCl, CdCl2, InCl2, SbCl3, ReCl5, OsCl3, IrCl3, PtCl4, and AuCl3 are mixed by ball milling. The ball milling time and ball milling speed of the raw materials are the same as those in Example 1, and Ru-Pd-Ag-Cd-In-Sb-Si-Re-Os-Ir-Pt-Au-P with a molar ratio of 0.02:0.05:0.05:0.05:0.05:0.1:0.2:0.21:0.05:0.05:0.03:0.04:0.3 is synthesized.

[0073] Example 12

[0074] The preparation method is consistent with that of Example 1, except that in the step of synthesizing carbon material-supported alloy A, MOFs, carbon black, sodium lignin sulfonate and sodium alginate are used to replace the carbon black in Example 1, and the mass ratio of MOFs: carbon black: sodium lignin sulfonate: sodium alginate is 1:1:1:1, and MOFs contains Cu, Ge, Sn and Fe elements, and the molar ratio of Cu:Ge:Sn:Fe is 1:1:1:1.

[0075] Example 13

[0076] The preparation method is consistent with that of Example 1, except that in the step of synthesizing carbon material-supported alloy A, sodium polyacrylate, alkali lignin, sodium citrate, sodium polystyrene sulfonate and sodium acrylate are used instead of the carbon black in Example 1, and the mass ratio of sodium polyacrylate: alkali lignin: sodium citrate: sodium polystyrene sulfonate: sodium acrylate is 3:2:2:1:1.

[0077] Embodiment 14

[0078] The preparation method is consistent with that of Example 1, except that the biomass raw material used is sugarcane bagasse.

[0079] Embodiment 15

[0080] The preparation method is consistent with that of Example 1, except that the biomass raw material used is nut shell.

[0081] Example 16

[0082] The preparation method is consistent with that of Example 1, except that in the step of synthesizing the carbon material-supported alloy A, pyrolysis is performed in a tubular furnace at 700°C under an argon atmosphere and the argon atmosphere is kept flowing, and the heating rate is 5°C·min -1 , the residence time is 4h.

[0083] Embodiment 17

[0084] The preparation method is consistent with that of Example 1, except that in the step of preparing hard carbon, the drying temperature is 100°C, the drying time is 48h, the carbonization is carried out at 1200°C in a nitrogen atmosphere for 3h, and the heating rate in a tube furnace is 8°C·min -1 , nitrogen flow rate is 180mL·min -1 , and finally at 300 r·min -1 The carbonized particles were ball milled at a rotation speed of 8 h, and then the product was passed through a 325-mesh sieve.

[0085] Embodiment 18

[0086] The preparation method is consistent with that in the embodiment, except that the mass fraction ratio of alloy A supported by the carbon material: carboxymethyl cellulose: styrene butadiene rubber is 95%: 3.5%: 1.5%; the mass fraction ratio of hard carbon: carboxymethyl cellulose: styrene butadiene rubber is 95%: 3.5%: 1.5%, the surface density of the first active material layer is 0.050 g / 1540.25 mm2, and the compacted density is 1.60 g / cm 3 The surface density of the second active material layer is 0.044 g / 1540.25 mm 2 , compacted density is 1.30g / cm 3 .

[0087] Embodiment 19

[0088] The preparation method is consistent with that in the embodiment, except that the mass fraction ratio of alloy A supported by the carbon material: carboxymethyl cellulose: styrene butadiene rubber is 98%: 1.0%: 1.0%; the mass fraction ratio of hard carbon: carboxymethyl cellulose: styrene butadiene rubber is 98%: 1.0%: 1.0%, and the surface density of the first active material layer is 0.070 g / 1540.25 mm 2 , compacted density is 2.10g / cm3 The surface density of the second active material layer is 0.054 g / 1540.25 mm 2 , compacted density is 1.80g / cm 3 .

[0089] Embodiment 20

[0090] The preparation method is consistent with that of Example 1, except that in Example 20, the amount of urea added is 0 g and the doping amount of N is 0%.

[0091] Embodiment 21

[0092] The preparation method is consistent with that of Example 1, except that in Example 21, the amount of phosphoric acid added is 0 g and the doping amount of P is 0%.

[0093] Embodiment 22

[0094] The preparation method is consistent with that of Example 1, except that in Example 22, the amount of phosphoric acid added is 0 g, the doping amount of P is 0%, the amount of urea added is 0 g, and the doping amount of N is 0%.

[0095] Comparative Example 1

[0096] The preparation method is consistent with that in Example 1, except that no carbon source is added in the second step of synthesis in Comparative Example 1, and the mass ratio of precursor E:carbon-containing substance B is 1:0.

[0097] Comparative Example 2

[0098] The preparation method is consistent with that in Example 1, except that in the second step of synthesis in Comparative Example 2, the precursor E is not added, and the mass ratio of the precursor E: the carbon-containing substance B is 0:1.

[0099] Comparative Example 3

[0100] The preparation method is consistent with that of Example 1, except that the first coating slurry is used to directly perform single-layer coating, and the surface density is twice that of the first coating in double-layer coating.

[0101] Comparative Example 4

[0102] The preparation method is consistent with that of Example 1, except that the second coating slurry is used to directly perform single-layer coating, and the surface density is twice that of the second coating in double-layer coating.

[0103] Comparative Example 5

[0104] The preparation method is consistent with that of Example 22, except that in Comparative Example 5, hard carbon is not prepared, but is replaced by graphite.

[0105] Comparative Example 6

[0106] The preparation method is consistent with that of Example 1, except that: the common hard carbon on the market is replaced, and P and N are doped according to the same method, and the preferred porosity is 20%.

[0107] Comparative Example 7

[0108] The preparation method is consistent with that of Example 1, except that: the common hard carbon on the market is replaced, and P and N are doped in the same way, and the porosity of the hard carbon is 60%.

[0109] The following performance tests were performed on the composite anode materials, negative electrode sheets and lithium-ion batteries obtained in the above Examples 1 to 22 and Comparative Examples 1 to 5, respectively.

[0110] 1. Cycle retention rate

[0111] ① Charge the battery to 4.5V at 0.5C at 25℃, with a cut-off current of 0.05C, and leave it for 5 minutes.

[0112] ②Measure the discharge capacity of the battery at this time and record it as D

[0113] ③Discharge the battery at 0.8C to 3V and leave it for 5 minutes

[0114] ④ Charge the battery to 4.5V at 1.5C, with a cut-off current of 0.05C, and leave it for 5 minutes

[0115] ⑤ Repeat the above steps ③④ for 400 times, and then measure the discharge capacity of the battery at this time, which is recorded as D

[0116] Cycle retention rate = D after / D before * 100%;

[0117] 2. Cyclic thickness change rate

[0118] ① Charge the battery to 4.5V at 0.5C at 25℃, with a cut-off current of 0.05C, and leave it for 5 minutes.

[0119] ②Measure the thickness of the battery at this time and record it as dfront

[0120] ③Discharge the battery at 0.8C to 3V and leave it for 5 minutes

[0121] ④ Charge the battery to 4.5V at 1.5C, with a cut-off current of 0.05C, and leave it for 5 minutes

[0122] ⑤ Repeat the above steps ③④ for 400 times, and then measure the thickness of the battery at this time, which is recorded as the cycle thickness retention rate after d = (d after - d before) / d before * 100%;

[0123] 3. First effect

[0124] Take the first charge capacity / first discharge capacity to get the first efficiency.

[0125] The above test results are shown in Table 1 below.

[0126] Table 1

[0127]

[0128]

[0129]

[0130]

[0131] Table 2. Low temperature discharge

[0132]

[0133] Table 3. Pole peeling force

[0134]

[0135] Table 1. It can be seen from the test results of Examples 1 to 3 and Comparative Examples 1 to 2 that the ratio of the precursor E of alloy A to the carbon-containing substance B will affect the first effect, electrode thickness and capacity retention rate of the material.

[0136] From the test results of Example 1 and Comparative Examples 3 to 4, it can be seen that the double-layer coating of the two materials, with the carbon material-supported alloy A as the bottom layer of the double-layer coating, can provide a higher energy density. Thanks to the close connection between the components of the alloy, the coordinated cooperation in stages, multiple levels and multiple platforms avoids the concentrated volume explosion of a single component. At the same time, using N-doped and P-doped hard carbon as the surface layer of the negative electrode material has a greater impact on the fast charging performance of the material, which can improve the fast charging performance of the material.

[0137] From the test results of Examples 1 and 4 to 7, it can be seen that when hard carbon is N-doped and P-doped, the conductivity of the negative electrode material and the initial efficiency of the lithium-ion battery in the scheme of the present invention can be greatly improved, the electron and lithium ion transport channels in the hard carbon are increased, and the capacity of the material is effectively improved.

[0138] From the test results of Examples 1 and 8 to 11, it can be seen that the change in the type and number of the metal salt C of the precursor E for preparing the alloy A will not substantially affect the performance of the negative electrode material as long as it does not exceed the scope of the technical solution disclosed in the present invention.

[0139] It can be seen from the test results of Examples 1 and 12 to 13 that, as long as the change of the carbon-containing substance B does not exceed the scope of the technical solution disclosed in the present invention, it will basically not affect the performance of the negative electrode material.

[0140] It can be seen from the test results of Examples 1 and 14 to 15 that the change of the biomass raw material will basically not affect the performance of the negative electrode material as long as it does not exceed the scope of the technical solution disclosed in the present invention.

[0141] It can be seen from the test results of Examples 1 and 16 to 17 that the change of the preparation conditions will not substantially affect the performance of the negative electrode material as long as it does not exceed the scope of the technical solution disclosed in the present invention.

[0142] It can be seen from the test results of Examples 1 and 18 to 19 that the change of coating parameters will not substantially affect the performance of the negative electrode material as long as it does not exceed the scope of the technical solution disclosed in the present invention.

[0143] From the test results of Example 22 and Comparative Example 5, it can be seen that the undoped hard carbon has a high conductivity and can be used as the top layer of the negative electrode plate in the solution of the present invention to improve the capacity and initial efficiency of the negative electrode material to a certain extent.

[0144] From the test results of Example 21 and Example 22, it can be seen that when hard carbon is doped with N, the conductivity of the negative electrode material and the initial efficiency of the lithium-ion battery described in the scheme of the present invention can be greatly improved, the electron and lithium ion transport channels in the hard carbon are increased, and the capacity of the material is effectively improved.

[0145] From the test results of Example 20 and Example 22, it can be seen that when hard carbon is doped with P, the electrical conductivity of the material described in the scheme of the present invention and the initial efficiency of the lithium-ion battery can be greatly improved, the electron and lithium ion transport channels in the hard carbon are increased, and the capacity of the material is effectively improved.

[0146] From the test results of Example 1 and Comparative Examples 6 to 7, it can be seen that when the porosity of hard carbon is too small, the expansion will increase. Due to the decrease in charging performance, the lithium ion channel is small, resulting in lithium expansion; when the porosity of hard carbon is too large, the first efficiency decreases significantly, but the expansion also increases significantly. This is because the compaction of high-porosity hard carbon does not reach the level of 1.80. During the rolling process, the hard carbon is damaged, thereby reducing the lithium ion channel. Therefore, the appropriate hard carbon porosity is conducive to reducing expansion.

[0147] Table 2, comparing Example 1 and Comparative Examples 3 to 5, it can be seen that the high entropy alloy needs to be matched with hard carbon to exert excellent low-temperature discharge performance. This is because the metal phase can improve the conductivity, the interface resistance remains relatively low and stable at different temperatures, and hard carbon as the upper material can play a good ion-conducting role, thereby improving the low-temperature discharge performance;

[0148] Table 3, comparing Example 1 and Examples 8 to 12, as well as Comparative Example 4, it can be seen that the high entropy alloy contains Cu, which, in the absence of a primer, enhances the peeling force of the electrode and prevents the upper hard carbon from falling off during the cycle;

[0149] In summary, the composite anode material of the present invention can greatly improve the conductivity of the material and the first efficiency of the lithium-ion battery, and effectively improve the capacity of the material, thereby greatly improving the cycle expansion rate, first efficiency and capacity retention rate of the lithium-ion secondary battery.

[0150] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A negative electrode plate, characterized in that: The negative electrode sheet comprises a current collector, on which a first active material layer and a second active material layer are sequentially coated, the first active material layer is located between the current collector and the second active material layer, the gram capacity of the first active material layer is greater than the gram capacity of the second active material layer, and the expansion rate of the first active material layer is greater than the expansion rate of the second active material layer; The first active material layer includes an alloy A supported by a carbon material, wherein the alloy A is a solid solution alloy; The second active material layer includes hard carbon; The alloy A includes Si x M y , wherein x:y is 0.05mol~0.2mol:0.05mol~1.4mol, wherein M includes three or more elements selected from vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, arsenic, aluminum, phosphorus, boron, ruthenium, rhodium, palladium, silver, cadmium, indium, tin, antimony, rhenium, osmium, iridium, platinum and gold, and M includes at least one element selected from vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, aluminum, ruthenium, rhodium, palladium, silver, cadmium, indium, tin, antimony, rhenium, osmium, iridium, platinum and gold.

2. The negative electrode sheet according to claim 1, characterized in that The carbon material-supported alloy A is formed by calcining the precursor E of the alloy A and the carbon-containing substance B, wherein the carbon-containing substance B includes one or more of MOFs, carbon black, sodium lignin sulfonate, sodium alginate, sodium polyacrylate, alkali lignin, sodium citrate, sodium polystyrene sulfonate and sodium acrylate, and the metal elements in the MOFs include one or more of antimony, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, aluminum, ruthenium, rhodium, palladium, silver, cadmium, indium, tin, antimony, rhenium, osmium, iridium, platinum and gold, and the mass ratio of the precursor E of the alloy A to the carbon-containing substance B is 7:1 to 1:

1.

3. The negative electrode sheet according to claim 1, characterized in that: The porosity of the hard carbon is 30% to 50%, and / or The hard carbon is doped with nitrogen and / or phosphorus, the mass percentage of nitrogen doping is 1.0% to 2.0%, and the mass percentage of phosphorus doping is 1.5% to 2.7%.

4. The negative electrode sheet according to claim 3, characterized in that: In the hard carbon, the nitrogen source is a nitrogen-containing compound or multiple nitrogen-containing compounds composed of one or several elements among C, O and H and the element N, and the phosphorus source is a phosphorus-containing compound or multiple phosphorus-containing compounds composed of one or several elements among C, O and H and the element P, and the multiple types are two to five.

5. The negative electrode sheet according to claim 1, characterized in that: The first active material layer and the second active material layer also include a dispersant and a binder, and the mass fraction ratio of the alloy A supported by the carbon material: dispersant: binder is 95% to 98%: 1.0% to 3.5%: 1.0% to 1.5%; the mass fraction ratio of the hard carbon: dispersant: binder is 95% to 98%: 1.0% to 3.5%: 1.0% to 1.5%.

6. The negative electrode sheet according to claim 1, characterized in that: The surface density of the first active material layer is greater than the surface density of the second active material layer; and the compaction density of the first active material layer is greater than the compaction density of the second active material layer.

7. The negative electrode sheet according to claim 6, characterized in that: The surface density of the first active material layer is 0.050 g / 1540.25 mm 2 ~0.070g / 1540.25mm 2 , compacted density is 1.60g / cm 3 ~2.10g / cm 3 , and / or, The surface density of the second active material layer is 0.044 g / 1540.25 mm 2 ~0.054g / 1540.25mm 2 , compacted density is 1.30g / cm 3 ~1.80g / cm 3 .

8. A method for preparing a negative electrode sheet according to any one of claims 1 to 7, characterized in that: Prepare the carbon material-supported alloy A; use the carbon material-supported alloy A to prepare a first slurry; use hard carbon to prepare a second slurry; uniformly apply the first slurry on the upper and lower surfaces of the current collector by extrusion coating to prepare the first active material layer, and uniformly apply the second slurry on the outer surface of the first active material layer by extrusion coating to prepare the second active material layer, thereby obtaining the negative electrode sheet.

9. The method for preparing a negative electrode sheet according to claim 8, characterized in that: The carbon material-supported alloy A is prepared by the following steps: Step S1, subjecting silicon and metal salt C to ball milling reaction to generate the precursor E of the alloy A, which is then impregnated with carbon-containing material B, freeze-dried, crushed, and calcined, wherein the metal salt C includes three or more elements selected from vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, arsenic, aluminum, phosphorus, boron, ruthenium, rhodium, palladium, silver, cadmium, indium, tin, antimony, rhenium, osmium, iridium, platinum, and gold; Or in step S1, silicon element, metal salt C and non-metallic pure substance D are subjected to ball milling reaction to generate precursor E, which is then impregnated with carbon-containing substance B, freeze-dried, crushed and calcined. The metal salt C and non-metallic pure substance D include three or more elements of vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, arsenic, aluminum, phosphorus, boron, ruthenium, rhodium, palladium, silver, cadmium, indium, tin, antimony, rhenium, osmium, iridium, platinum and gold, and the metal salt C must include one element of vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, aluminum, ruthenium, rhodium, palladium, silver, cadmium, indium, tin, antimony, rhenium, osmium, iridium, platinum and gold.

10. The method for preparing a negative electrode sheet according to claim 9, characterized in that: In step S1, at least one of the following conditions is met: (a) In step S1, the metal salt C comprises one or more of sulfate, nitrate or chloride; (b) In step S1, the carbon-containing substance B includes one or more of MOFs, carbon black, sodium lignin sulfonate, sodium alginate, sodium polyacrylate, alkali lignin, sodium citrate, sodium polystyrene sulfonate and sodium acrylate, and the metal elements in the MOFs are composed of one or more of vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, aluminum, ruthenium, rhodium, palladium, silver, cadmium, indium, tin, antimony, rhenium, osmium, iridium, platinum and gold; (c) In step S1, the ball milling time of the precursor E of the alloy A is 8 h to 20 h, and the ball milling speed is 300 rpm / min to 500 rpm / min; (d) In step S1, during the impregnation, the mass ratio of the precursor E of the alloy A to the carbon-containing substance B is 7:1 to 1:1, the impregnation time is 5 h to 10 h, and the calcination step comprises: pyrolysis in a tubular furnace at 700° C. to 900° C. under a protective atmosphere while maintaining the protective atmosphere flowing, and the heating rate is 5° C. min. -1 ~10℃·min -1 , the residence time is 2h to 4h, and the protective atmosphere is argon atmosphere, helium atmosphere or nitrogen atmosphere.

11. The method for preparing a negative electrode sheet according to claim 8, characterized in that: The preparation of the first slurry comprises: mixing the dispersant and the alloy A supported by the carbon material and stirring them uniformly, and finally adding the binder and stirring to obtain the first slurry; the mass fraction ratio of the alloy A supported by the carbon material: the dispersant: the binder is 95% to 98%: 1.0% to 3.5%: 1.0% to 1.5%, and / or, The preparation of the second slurry includes: mixing the dispersant and the hard carbon evenly, and finally adding the binder, and stirring to obtain the second slurry: the mass fraction ratio of the hard carbon: dispersant: binder is 95% to 98%: 1.0% to 3.5%: 1.0% to 1.5%.

Citation Information

Patent Citations

  • Lithium ion secondary cell negative electrode active-material, preparation method of lithium ion secondary cell negative electrode active-material, lithium ion secondary cell negative electrode pole and lithium ion secondary cell

    CN103855368A

  • Negative active material, negative electrode, lithium battery and method for manufacturing the negative active material

    CN104810510A

  • Preparation method and applications of porous anode material for lithium ion battery

    CN106784766A

  • Negative electrode material for lithium ion battery, preparation method of negative electrode material and lithium ion secondary battery

    CN107681125A

  • Silicon-based alloy carbon composite negative electrode material, preparation method thereof and application thereof

    CN109950522A

Cited By

  • Positive plate and lithium ion battery

    CN121662740A

  • Positive electrode sheet and lithium ion battery

    CN121662740B